Au bla plei baskitbol - McCartney, Delma ([Katherine, N.T.] : Barunga Press, 1985)
Kriol reader.
Text in Kriol.
Keywords: Kriol language -- Readers; Language - Change; Language - Kriol; Education - Language - Indigenous languages - Readers and primers; Kriol language; Sport - Basketball; Arnhem Land (NT); Australian